Competence of Courts of First Instance in the Republic of Tajikistan - Zainashev, Ravil; Gilmanov, Idris; Gilmanov, Muhamat (Journal of History Culture and Art Research, 2018)
Issues of jurisdiction competence of courts on criminal cases in the territory of the Russian Federation are regulated by Article 31 from the Code of Criminal Procedure of the Russian Federation. The rules of this article are of great importance, since they comply with the requirements of international documents of the United Nations. Indeed, the first question to be answered by a judge in a case is whether it is subject to the given court. Thus, compliance with the requirements of Article 31 from the Code of Criminal Procedure of the Russian Federation consists in the fact that in case of violation of the rules of this article, this automatically leads to the cancellation of a verdict and the second consideration of the criminal case. The issues of the competence of the courts of first instance also receive serious attention from the legislators of the Republic of Tajikistan. The legal system of this country is included in the Romano-German legal family, but with distinctive features. In our opinion, in order to facilitate the workload of the courts of first instance it is necessary to introduce misdemeanors in Article 18 of the Criminal Code of the Republic of Tajikistan as an independent form of punishment. In addition, for the same purpose it is necessary to provide for the simplified (summary) proceedings in the Criminal Procedure Code of the Republic of Tajikistan, which, unfortunately, is absent in the current legislation.